Agro-Morphological Trait Characterization of Selected Soybean [Glycine Max (L.) Merr.] Accessions at Dabus in Assosa (Indian Journal of Advanced Botany (IJAB), 2025)
As study Soybean is the most important and widely grown legume crop worldwide with its multipurpose use and grows in the tropical, subtropical and temperate climates. In Ethiopia, soybean is becoming a high potential promising crop for the development of agricultural sectors. Targeting variety selection in its growing environments is the prime interest of any plant breeding program with respect to important parameters of morphological traits. Twenty soybean accessions were obtained from three geographic areas of Assosa and laid out in a randomized complete block design with three replications. Higher phenotypic and genotypic variance was observed for grain yield. Branches per plant, pods per plant, seeds per pod and grain yield had higher PCV while plant height exhibited moderate PCV. Genotypic coefficient variance was high for pods per plant and grain yield whereas plant height and seeds per pod showed moderate GCV. Days to flowering and maturity, plant height, pods per plant and seeds per pod had high heritability whereas relatively moderate H2 was recorded for HSW and grain yield. Significant genetic variability in mean performance of all the traits under studied material indicated that genotypes have considerable amounts of genetic variation that could be used for further breeding programs in variety development. Finally, characterization of soya bean accession with genotype of GDM7 had highest 2478kg/ha grain yield and this accession is recommended for better adaptation and yield for cultivation of farmers’ in Assosa zone and similar agro ecology in Ethiopia.